Exploring Overactive Bladder Symptoms in Premenopausal and Postmenopausal Women: A Comparative Cross-Sectional Study - Tural, Egemen; Ertürk Coşkun, Ayşe Deniz; Pınar, Gizem; Vural, Fisun (Makara Journal of Health Research, 2024)
Background: Overactive bladder syndrome affects millions globally. It can intermittently cause urinary incontinence, which can significantly diminish the quality of life. This study investigated overactive bladder symptoms in premenopausal and postmenopausal individuals by analyzing the influence of demographic, gynecological, and obstetric factors. Methods: This single-center prospective cross-sectional study was conducted between September 1 and November 1, 2023, among premenopausal and postmenopausal women. In total, 244 patients meeting the inclusion criteria were selected using a simple random method. Participants were asked to complete an information collection form, and the Turkish version of the Overactive Bladder-V8 questionnaire was administered. A significance level of p < 0.05 was considered. Results: Individuals with an overactive bladder were older (mean age, 46.14 ± 14.56) and had a higher body mass index (mean, 28.47 ± 6.02) than healthy individuals (p = 0.013, p < 0.001, respectively). No significant difference in menopausal status was found (p = 0.091). Urinary incontinence was significantly higher in the overactive bladder group (63.6% vs. 17.4%, p < 0.001). The number of vaginal deliveries and prior gynecologic surgeries differed significantly between the groups (p = 0.030, p = 0.001, respectively). Conclusions: Age, higher body mass index, vaginal childbirth, and history of gynecological surgeries are associated with overactive bladder frequency, whereas menopausal status did not exert a significant effect.